1996
DOI: 10.7326/0003-4819-124-12-199606150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hepatitis C Viremia Predicts Late Relapse after Sustained Response to Interferon-α in Chronic Hepatitis C

Abstract: Patients with chronic hepatitis C should be tested for serum HCV RNA 1 year after a sustained biochemical response to interferon-alpha therapy to determine whether the response is complete and permanent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 0 publications
7
49
0
Order By: Relevance
“…Long-term follow-up studies showed that the vast majority of the sustained virologic responders are probably cured from HCV infection. [44][45][46] HCV resistance is defined as HCV RNA persistence in serum after therapy. The incidence of HCV resistance to IFN-based therapies varies according to the administered regimen.…”
Section: Definitions: Incidence and Patterns Of Hcv Resistance To Antmentioning
confidence: 99%
“…Long-term follow-up studies showed that the vast majority of the sustained virologic responders are probably cured from HCV infection. [44][45][46] HCV resistance is defined as HCV RNA persistence in serum after therapy. The incidence of HCV resistance to IFN-based therapies varies according to the administered regimen.…”
Section: Definitions: Incidence and Patterns Of Hcv Resistance To Antmentioning
confidence: 99%
“…[10][11][12] They thus concluded that in patients with chronic hepatitis C who have no detectable serum HCV RNA 24 weeks after interferon therapy, longterm sustained biochemical and virologic response is anticipated. However, whether HCV SVR24 could be maintained in patients with chronic hepatitis B and C coinfection has not been reported.…”
mentioning
confidence: 99%
“…Hepatitis C-Reports describing the results of controlled trials suggested that interferon alpha therapy was associated with a 50% biochemical response rate, a 50% relapse rate in responders, and a sustained response rate of 25% (95). Patients who do not respond to therapy within the first 3 months are unlikely to respond thereafter.…”
Section: Treatment Of Viral Hepatitismentioning
confidence: 99%